Design of Short Synchronization Codes for Use in Future GNSS System. (6th May 2008) - Shanmugam, Surendran K.; Mongrédien, Cécile; Nielsen, John; Lachapelle, Gérard
Abstract : The prolific growth in civilian GNSS market initiated the modernization of GPS and the GLONASS systems in addition to the potential deployment of Galileo and Compass GNSS system. The modernization efforts include numerous signal structure innovations to ensure better performances over legacy GNSS system. The adoption of secondary short synchronization codes is one among these innovations that play an important role in spectral separation, bit synchronization, and narrowband interference protection. In this paper, we present a short synchronization code design based on the optimization of judiciously selected performance criteria. The new synchronization codes were obtained for lengths up to 30 bits through exhaustive search and are characterized by optimal periodic correlation. More importantly, the presence of better synchronization codes over standardized GPS and Galileo codes corroborates the benefits and the need for short synchronization code design.